Actualization of Indonesian Economic and Cultural Development Reviewed from Ibn Khaldun's Thoughts - Kusuma, Nurul Rahmah; Janwari, Yadi; Jubaedah, Dedah; Maulana, Fauzan Aziz (Mimbar Agama Budaya, 2024)
The problem of poverty in Indonesia is very complex which can trigger economic and socio-cultural problems, namely that there is a poor population of 9.36 percent. This indicates that prosperity has not been achieved in economic development in Indonesia. Ibnu Khaldun explained that a developed country is determined by the strength of the government implementing sharia and justice which is implicitly in accordance with the ideals of national development in Indonesia. The aim of this research is to analyze the actualization of Indonesia's economic development in terms of Ibnu Khaldun's thoughts. The research method used is qualitative library research sourced from secondary data using library research techniques from Muqaddimah books, journal articles and various kinds of relevant library materials which are then analyzed using descriptive analysis methods. The results of this research are that Indonesia's economic development has not yet achieved economic and socio-cultural balance as stated by Ibnu Khaldun. This is based on an imbalance between state revenues and government expenditure. The high taxes imposed on the public cannot yet be directly proportional to state spending which should be able to reduce inequality, poverty and so on, especially in underdeveloped areas.